"By a silken thread": Regional banking integration and pathways to financial development in Japan's Great Recession - Mathias Hoffmann; Toshihiro Okubo (University of Zurich, Department of Economics, 2012)
How do financial development and financial integration interact? We focus on Japan's Great Recession after 1990 to study this question. Regional differences in banking integration affected how the recession spread across the country: financing frictions for credit-dependent firms were more severe in less integrated prefectures, which saw larger decreases in lending by nationwide banks and lower GDP growth. We explain these cross-prefectural differences in banking integration by reference to prefectures' different historical pathways to financial development. After Japan's opening to trade in the 19th century, silk reeling emerged as the main export industry. The silk reeling industry depended heavily on credit for working capital but comprised many small firms that could not borrow directly from larger banks. Instead, silk merchants in Yokohama, the main export hub for silk, provided silk reelers with trade loans. Many regional banks in Japan were founded as local clearing houses for such loans, and regional banks continued to account for above-average shares in lending in the formerly silk-exporting prefectures long after the decline of the silk industry. Using the cross-prefectural variation in the number of silk filatures in 1895 as an instrument, we confirm that the post-1990 decline was worse in prefectures where credit constraints were tightened through low levels of banking integration. Our findings suggest that different pathways to financial development can lead to long-term differences in de facto financial integration, even if there are no formal barriers to capital mobility between regions, as is the case in modern Japan.
Keywords: F15; F30; F40; G01; N15; N25; O16; 330; financial development; financial integration; Japan; Great Recession; Lost Decade; banking integration; regional business cycles; transmission of financial shocks; misallocation of credit; trade credit; export finance; silk industry; Bankenregulierung; Bankenkrise; Schock; Kreditgeschäft; Unternehmensfinanzierung; Textilindustrie; Japan